THE USE OF GENETIC RESOURCES TO INCREASE THE EFFICIENCY OF POTATO BREEDING - E. A. Simakov; V. A. Zharova; A. V. Mityushkin; V. A. Biryukova; E. V. Rogozina; S. D. Kiru (Труды по прикладной ботанике, генетике и селекции, 2018)
To expand the genetic basis of newly created varieties of potatoes a complex interspecific hybrids from VIR (N. I. Vavilov All-Russian Institute of Plant Genetic Resources) were used as parental lines that combine resistance to the most harmful pathogens with a complex of valuable commercial traits in progeny from crosses with breeding varieties. This provides the possibility to identify transgressive recombinants and increases the efficiency of selection of new promising varieties with different maturity and target use.